Development, validation and evaluation of the usm insulin adherence module (USM-IAM) among patients with uncontrolled type 2 diabetes mellitus - Zainudin, Aida Maziha (2024)
Many patients with type 2 diabetes mellitus do not achieve the desired glycemic control despite insulin treatment, likely due to an improper understanding of insulin function, its intensification process, and patients’ negative perceptions. We developed a USM-insulin adherence module (USM-IAM) to educate patients. This study involved a combination of qualitative and quantitative research. The first phase, namely, an exploration of patients’ knowledge and problems related to insulin therapy, utilised focus group discussion to collect information from patients. Phase 2: Development and validation of the USM-insulin adherence module. In this phase, a literature search was carried out, and the researcher identified a list of factors interfering with insulin adherence. The factors were combined with the findings from focus group discussions to produce an insulin adherence module. Content validation (CVI) by experts and face validation by patients (FVI) was subsequently performed. The third phase was the evaluation of the effectiveness of the USM-IAM. This RCT assessed the effect of USM-IAM-based counselling on adherence score, HbA1c and FBS compared to standard counselling. Patients were allocated to groups based on computer randomisation. Four diabetes educators counselled patients during endocrine clinic sessions. Patients received counselling on V1 and V2. Blood investigations and adherence scores were obtained at V1, V2 and V3. Three themes emerged from the focus group discussions. The newly developed module consists of five units and 20 items. The CVI and FVI of the module were good. In phase three, 180 patients were recruited. Ninety patients were randomised to each group. The baseline sociodemographic and clinical characteristics were homogenous among groups. Over the course of the study, significant improvements were noted in IAQDM scores, FBS, and HbA1c levels from baseline to both the third and sixth months for all participants, irrespective of their group allocation. Within group analysis showed a statistically significant improvement in the adherence scores and HbA1c from baseline to the third and sixth months for both groups. However, FBS changes within the control group were not significant. Between the third and sixth months, no significant changes were noted in any outcomes for either group. While differences between the groups were not statistically significant, the intervention group demonstrated greater improvement across all outcomes. In conclusion, patients had poor knowledge of diabetes and insulin. The USM-IAM has good CVI and FVI. Both groups had increased adherence scores and reduced FBS and HbA1c levels, with greater changes observed in the intervention group.